2021
DOI: 10.1371/journal.pone.0250821
|View full text |Cite
|
Sign up to set email alerts
|

Health determinants among refugees in Austria and Germany: A propensity-matched comparative study for Syrian, Afghan, and Iraqi refugees

Abstract: In recent years, Germany and Austria have been among the leading European receiving countries for asylum seekers and refugees (AS&R). The two countries have cultural and economic similarities, but differ, for example, in their health care systems, with AS&R having unrestricted access to health services upon arrival in Austria, but not in Germany. This study investigates the determinants of health among refugees in Austria and Germany, and how these determinants differ between the two countries. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
0
9
1
Order By: Relevance
“…As the third most common country of origin, the UN Refugee Agency (UNHCR) recorded around 2.7 million Afghan refugees recognized under international law, and 0.3 million asylum seekers currently awaiting legal recognition, in 2019 (UNHCR, 2020 ). Compared to refugee populations from other countries of origin in Austria, Afghans report particularly low health (Georges, Buber-Ennser, Rengs, Kohlenberger, & Doblhammer, 2021 ). Prolonged, repeated, and/or interpersonal traumatic experiences in the country of origin or during flight are highly prevalent among refugees (Bogic, Njoku, & Priebe, 2015 ), with between 40 and 90% reporting at least one traumatic experience, depending on the sample and location (Scoglio & Salhi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the third most common country of origin, the UN Refugee Agency (UNHCR) recorded around 2.7 million Afghan refugees recognized under international law, and 0.3 million asylum seekers currently awaiting legal recognition, in 2019 (UNHCR, 2020 ). Compared to refugee populations from other countries of origin in Austria, Afghans report particularly low health (Georges, Buber-Ennser, Rengs, Kohlenberger, & Doblhammer, 2021 ). Prolonged, repeated, and/or interpersonal traumatic experiences in the country of origin or during flight are highly prevalent among refugees (Bogic, Njoku, & Priebe, 2015 ), with between 40 and 90% reporting at least one traumatic experience, depending on the sample and location (Scoglio & Salhi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the present study, 67.4% of Syrian refugees in Ireland described their health to be either 'very good' or 'good' at the time of the study. The results from the other research, investigating self-reported health among newly arrived refugees, suggest variability in this regard, ranging from 58% in Norway to more than 70% in Germany and Austria [24,41]. However, the comparison with the overall health of the Irish population, where 83% of adults reported good overall health [42], indicates a health disparity between the refugee population and Irish nationals, even though the refugees had a younger age profile.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present study, 67.4% of Syrian refugees in Ireland described their health to be either ‘very good’ or ‘good’ at the time of the study. The results from the other research, investigating self-reported health among newly arrived refugees, suggest variability in this regard, ranging from 58% in Norway to more than 70% in Germany and Austria [ 24 , 41 ]. However, the comparison with the overall health of the Irish population, where 83% of adults reported good overall health [ 42 ], indicates a health disparity between the refugee population and Irish nationals, even though the refugees had a younger age profile.…”
Section: Discussionmentioning
confidence: 99%